2004
DOI: 10.1242/jeb.01286
|View full text |Cite
|
Sign up to set email alerts
|

Spatial vision in the echinoid genusEchinometra

Abstract: Although eyes are generally considered necessary for image resolution, a diffuse photoreceptive system with directional sensitivity may also have this ability. Two species of the echinoid genus Echinometra were tested for spatial vision by examining their ability to locate and move towards targets of different sizes. The echinoids were significantly oriented (P<0.0001) towards a target with an angular width of 33°(0.3·sr) but were not oriented to targets with angular widths of 26°and 16°. This ability is proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 13 publications
5
66
0
Order By: Relevance
“…We found them to be primarily arranged in two clusters in the numerous tube feet and to fulfill the minimal requirements for directional vision by deploying the sea urchin opaque skeleton as a screening device. Taken together, our data support a model of "compound-eye"-like vision in sea urchins contrasting to those proposed for echinoderms by other authors in the past (3,12,13). Our findings furthermore constitute unique documentation of a deuterostome animal deploying r-opsinexpressing PRCs for vision.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…We found them to be primarily arranged in two clusters in the numerous tube feet and to fulfill the minimal requirements for directional vision by deploying the sea urchin opaque skeleton as a screening device. Taken together, our data support a model of "compound-eye"-like vision in sea urchins contrasting to those proposed for echinoderms by other authors in the past (3,12,13). Our findings furthermore constitute unique documentation of a deuterostome animal deploying r-opsinexpressing PRCs for vision.…”
supporting
confidence: 83%
“…The spatial resolution of the PRC system would then depend on the spacing of spines that function, similarly to pigment cells in insect ommatidia, by shading defined parts of the sea urchin's skin. In contrast, our findings of distinct PRCs contradict the prerequisite of the model proposed by Johnsen and colleagues (3,13) and are supported by the findings of Millott and Coleman (35), who demonstrated that the podial bases in sea urchins comprise the most photosensitive part of their skin. Our finding that the basal PRC cluster is embedded in a considerable depression of the tube foot pore, resulting in a smaller angular width of the light reaching the PRCs (Fig.…”
Section: Different Compound Eye Models In Echinodermssupporting
confidence: 72%
See 1 more Smart Citation
“…Orientation to visual stimuli in echinoderms occurs in one species of starfish, L. laevigata (Garm and Nilsson 2014) and two species of sea urchins (Blevins and Johnsen 2004;Yerramilli and Johnsen 2010). In addition, physiological studies have reported phototactic movements in the northern Pacific seastar, Asterias amurensis Ohtsuki 1966, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Blevins and Johnsen tested this hypothesis using echinoids of the genus Echinometra and found that their visual resolution was on the order of that predicted by the spacing of their spines (~30deg.) (Blevins and Johnsen, 2004).This paper examines the visual resolution of S. purpuratus. Like Echinometra, it exhibits shelter-seeking behavior and is known to have a photosensitive test.…”
mentioning
confidence: 99%